Association of lipoprotein (a) with lipid profile and response to statin treatment in hyperlipidemic patients - Ammara Abid; Amina Nadeem (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine serum levels of lipoprotein(a) in the local population, its relationship with other parameters of lipid profile and statins’ response to lipoprotein(a). Method: The cross-sectional analytical study was conducted at the Pak-Emirates Military Hospital and Army Medical College, Rawalpindi, Pakistan, from March 2018 to March 2019, and comprised healthy controls in group I, persons with hyperlipidemia without medications in group II, and diagnosed cases of hyperlipidemic on statin therapy in group III. The samples were studied using enzyme-linked immunosorbent assasy for lipoprotein(a) estimation, and an automated chemistry analyser for lipid profile estimation. Data was analysed using SPSS 21. Results: Of the 90 subjects with a mean age of 43±5 years, 30(33.3%) were in each of the three groups. Mean body mass index, total cholesterol, triglycerides and low-density lipoprotein were significantly different among the groups. Lipoprotein(a) level was not correlated with statins (p>0.05), but had a positive correlation with low-density lipoprotein. Conclusion: Lipoprotein(a) was found to be raised even in the absence of dyslipidemia, and it was controversially raised with statin therapy. Lipoprotein(a) can very well be regarded as an independent risk factor for all the known complications of hyperlipidemia. Key Words: Hyperlipidemia, BMI, Statins, Lipid profile, Lipoprotein(a).